Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(4510 x 520 ) / 7515=243
(0.8)5 / (0.4)6=0
215 x 94 / 66 x 83=9
\(\frac{45^{10}.5^{20}}{75^{15}}=\frac{\left(3^2.5\right)^{10}.5^{20}}{\left(3.5^2\right)^{15}}=\frac{3^{20}.5^{10}.5^{20}}{3^{15}.5^{30}}=\frac{3^{20}.5^{30}}{3^{15}.5^{30}}=3^5=243\)
\(\frac{\left(0,8\right)^5}{\left(0,4\right)^6}=\frac{\left(0,4.2\right)^5}{\left(0,4\right)^6}=\frac{\left(0,4\right)^5.2^5}{\left(0,4\right)^6}=\frac{2^5}{0,4}=\frac{32}{\frac{2}{5}}=32.\frac{5}{2}=80\)
\(\frac{2^{15}.9^4}{6^6.8^3}=\frac{2^{15}.\left(3^2\right)^4}{\left(2.3\right)^6.\left(2^3\right)^3}=\frac{2^{15}.3^8}{2^6.3^6.2^9}=\frac{2^{15}.3^8}{2^{15}.3^6}=3^2=9\)
a. 2/3+ -1/6
=4/6+ -1/6 = 1/2
b.5/4 - 3/16
=20/16-3/16 = 17/16
c.1/2+ (4/5 - 1/2)
= 1/2+ 4/5 -1/2= 1/2- 1/2 +4/5
=0+4/5= 4/5
d. (0.5-3/4) . (1/5 - 0.4)
= (1/2- 3/4) . (1/5-2/5)
=(2/4 - 3/4) . (1/5 - 2/5)
= 1/4 . 1/5= 1/20
e. 3/5 . 7/13 - 3/5. 18/13
= 3/5. (7/13 - 18/13)
= 3/5. -11/13= -33/65
#hoctot
`a)2/3+ -1/6=(2xx2)/(3xx2)+ -1/6=4/6+ -1/6=1/2`
`b)5/4-3/16=20/16-3/16=17/16`
`c)1/2+(4/5-1/2)=1/2+4/5-1/2=1/2-1/2+4/5=0/4+4/5=4/5`
`d)(0,5-3/4)xx(1/5xx0,4)=(1/2-3/4)xx(1/5-2/5)=(2/4-3/4)xx(1/5-2/5)=-1/4xx-1/5=1/20`
`e)3/5xx7/13-3/5xx18/13`
`=3/5xx(7/13-18/13)`
`=3/5xx11/13`
`=33/65`
$#Lani2011$
Chức bn học tốt
Đề bài: Tìm x
\(\frac{2}{3}x-0.4=\frac{1}{5}\)
\(\frac{2}{3}x-0=\frac{1}{5}\)
\(\frac{2}{3}x=\frac{1}{5}\)
\(x=\frac{1}{5}\div\frac{2}{3}\)
\(x=\frac{1}{5}.\frac{3}{2}\)
\(x=\frac{3}{10}\)
Vậy \(x=\frac{3}{10}.\)
Bài làm:
\(\frac{2}{3}x-0.4=\frac{1}{5}\)
\(\Leftrightarrow\frac{2}{3}x-\frac{2}{5}=\frac{1}{5}\)
\(\Leftrightarrow\frac{2}{3}x=\frac{3}{5}\)
\(\Leftrightarrow x=\frac{3}{5}\div\frac{2}{3}\)
\(\Rightarrow x=\frac{9}{10}\)
Học tốt!!!!
\(\frac{x}{5}+0,4=1+\frac{6}{5}\)
\(\Leftrightarrow\frac{x}{5}+\frac{2}{5}=\frac{5}{5}+\frac{6}{5}\)
\(\Leftrightarrow x+2=5+6\)
\(\Leftrightarrow x+2=11\Leftrightarrow x=9\)
\(\frac{x}{5}+0,4=1+\frac{6}{5}\)
=> \(\frac{x}{5}+\frac{5\cdot0,4}{5}=\frac{11}{5}\)
=> \(\frac{x}{5}+\frac{2}{5}=\frac{11}{5}\)
=> \(\frac{x+2}{5}=\frac{11}{5}\)
=> x = 9